Concept of Modern Islamic Education According to KH. Abdul Wahid Hasyim - Lulut Julianto; Siti Choiriyah (al-Afkar, Journal For Islamic Studies, 2025)
Wahid Hasyim is a phenomenal figure in the history of the nation's journey, even though it only lasted a short time because he died when he was 39 years old. In the midst of his many thinkers and work in fulfilling independence, Wahid Hasyim also contributed to the nation's next journey. Because even though his body is gone, ideas are continued by subsequent generations, especially by his own son, KH. Abdurrahman Wahid. In the context of education, he also made many changes in his thinking. This can be seen after returning from Mecca when making changes to his father's Islamic boarding school, for example his teaching methods. As well as opening up freedom for students to study various scientific disciplines, especially in mastering foreign languages, Arabic and English, but still using Indonesian well. The four pillars of education (religion, development of students' potential, social and national spirit) contributed by Wahid Hasyim in the Islamic education system are things that need to be continued amidst the nation's decline. Wahid Hasyim teaches education with an attitude of respect for differences, a sense of nationalism, pluralism and multiculturalism in Indonesia.